Integration to the Environment and Preservation of Identity: Exogamy in the Community of Valparaiso-Viña del Mar (Chile), 1950-2000 - Estrada, Baldomero (Cuadernos de Historia, 2021)
This research is a study of the process of integration of the Jewish community of Valparaíso-Viña del Mar to the receiving society. The increasing in exogamous marriages (between Jews and those who are not) can be interpreted as an indicator of integration of the Jewish community into the host society. However, from a more careful analysis of these exogamous marriages, an interesting diversity is discovered that raises greater variables in terms of the conclusions that can be drawn from the relationship between exogamous marriages and integration into the host society by the community Jewish migrant. The cultural transformations of the environment and the demographic decrease of the community facilitate a greater tendency to exogamous marriages without necessarily meaning loss of their Jewish identity.